Letters from a revolution ([Quezon City] ABS-CBN Current Affairs, 2001)
Traces the contexts within which the two People Power revolutions happened and the way these events changed Philippine politics and society.
VHS.
Ed Lingao, writer and executive producer ; Patrick Paez, Anne Torres, writers.
Randy S. David, host.
Keywords: Philippines -- Politics and government; Martial law -- Philippines; Philippines -- History -- Revolution, 2001.; Philippines -- History -- Revolution, 1986.